Nutritional Status of Children with Attention Deficit Hyperactivity Disorder: A Pilot Study - Joy Y. Kiddie; Margaret D. Weiss; David D. Kitts; Ryna Levy-Milne; Michael B. Wasdell (International Journal of Pediatrics)
Objectives. This is a pilot study of the dietary intake and nutrient status of children with Attention Deficit Hyperactivity Disorder (ADHD). Method. Nutritional assessment of 43 children aged 6–12 with ADHD was performed using a 3-day food record, 24-hour recall, and serum assessors. Results. Macronutrient intake and consumption of Low-Nutrient Foods were comparable to population norms; however, 66% were found to be deficient in zinc and 23% in copper. Conclusions. This pilot study reports the food intake and nutrient status of children with ADHD and shows a predisposition for low zinc and copper status in ADHD.